CHARLES SANDERS PEIRCE’S TRICHOTOMY OF OBJECT IN THE FREE PALESTINE CAMPAIGN POSTERS FROM PINTEREST - Fauziyah, Dalfa; Nurhapitudin, Irman; Sakinah, R. Myrna Nur (Journal of Research on Language Education, 2025)
This research explores semiotic analysis by focusing on the trichotomy of object including icon, index, and symbol found in the Free Palestine campaign posters, emphasizing their role in conveying messages in visual media about the campaign. The visual media are posters that effectively disseminate information and mobilize support through social media platforms. This research uses a qualitative method, by analyzing five selected posters taken from the pinterest platform that reflect the campaign theme. Using Charles Sanders Peirce's trichotomy of object regarding icons, indexes, and symbols, this analysis reveals how each poster uses different visual elements to communicate a comprehensive narrative. The analysis showed that of the five posters studied, a total of 9 icons, 8 indexes, and 7 symbols were identified. The conclusion of this study shows that the combination of visual representations and symbolic meanings in the posters serves not only as a communication tool, but also as a powerful act of support for the liberation of Palestine. Keywords: Charles Sanders Peirce; Free Palestine Campaign Posters; Semiotics; Trichotomy of Object